Morphometric parameters of the distal end of the femur and their influence on the knee joint - Valcic, Vanja (Medicinski podmladak, 2022)
Introduction: The femur is a long pair of bones and it consists of the proximal, distal end and body. The distal end carries the medial and lateral condyle (Condylus medialis et lateralis), the intercondylar fossa and line (Linea et fossa intercondylaris), and together with the patella (Patella) and tibia (Tibia) forms the knee joint. This study considers the effects of certain parameters present on the femurs on the knee joint, and in addition to the fact that anthropometrically important parameters, they also represent important clinical indications during operations on the knee joint, which become necessary due to the consequences of various diseases or environmental factors.Aim: Study of morphometric parameters of the distal end of the femur which are of exceptional importance in orthopedic surgery of the hip joint when planning osteocorrective interventions.Material and methods: At the Institute for Anatomy "Niko Miljanić" in Belgrade in 2020, 47 femurs were measured, of which 22 were right and 25 were left. Shaft length, lateral distal femoral angle (LDFA), mechanical lateral distal femoral angle (mLDFA) were measured, and for all measurements an orthopedic digital goniometer accurate to two decimal places was used.Results: A total of 47 femurs with an average shaft length of 40.0 ± 2.69 were processed. The shortest specimen was 34.8 cm while the longest was 45.7 cm. The mean LDFA was 81.36 ±2.95 degrees, the minimum was 81.8 degrees while the maximum was 89.9 degrees. The average mLDFA was 87.69 ± 2.99 degrees, while the maximum and minimum were 94.6 and81.8 degrees, respectively. Conclusion: Thirteen measured femurs fell under the definition of either Genu varum or Genu valgum. Of these, four right and three left femurs are defined as varum, while two right and four left are defined as valgum. Additional analysis is necessary to determine the clinical implications of these parameters.
Keywords: Femur, knee, knee joint, Genu Varum, Genu Valgum